ChemInform Abstract: Extended Structural Materials Composed of Transition‐Metal‐Substituted Arsenicniobates and Their Photocatalytic Activity. Issue 32 (August 2015) - Lan, Qing; Zhang, Zhi‐Ming; Li, Yang‐Guang; Wang, En‐Bo
Abstract The novel cluster compounds [Cu(en)2(H2O)] [Cu(en)2] 4AsNb9V7O44 ·8H2O (I) and [Cu(en)2(H2O)] [Cu(en)2] 4HAsNb8V8O44 ·11H2O (II) are prepared in 41 and 38% yield, resp., by solvothermal reaction of K7HNb6O19, Cu(OAc)2, Na2VO3, As2O3, and en under nearly identical conditions (HCl, H2O, autoclave, 160 °C, 5 d) except for the pH value which should be in the range 10.3—10.6 for (I) and 10.7—11.0 for (II).